Scholarly Research and Applied Approach to the Interdependence of Manufacture and Transportation of Products Based on Intermodality and Multimodality - Laiko, O.; Ilchenko, S.; Maslii, N.; Demianchuk, M. (Science and Innovation, 2023)
Introduction. The integration processes of the transport system are an important factor in the economic development of Ukraine in conditions of increased competition for transit cargo flows. Therefore, it is necessary to develop multimodal transportation of products to ensure the competitiveness of Ukraine in the international transport market. Problem Statement. In the modern conditions of the development of the transport system of Ukraine, there have arisen theoretical and applied problems related to determining the most appropriate means for hybrid cargo transportation. Purpose. This study is aimed at identifying the interdependence of the sphere of manufacture and transportation of products in order to determine and justify the most efficient means of organization of intermodal and multimodal cargo transportation. Material and Methods. The review of existing scientific developments is based on systematic approach and comparative historical analysis of the transport economy, given the economic, geographical, and geopolitical position of Ukraine. The verification and falsification methods, as well as the economic and mathematical analysis and modeling have been used to substantiate the scholarly and applied approach. Results. The theoretical and practical problems of the transport economy development have been analyzed. The trends in the development of cargo transportation by various means of transport have been identified. The dependence of the products sold (goods, services) on the products transported by means of transport has been simulated. The types of activities, which require transport services and are significant for the national economy have been analyzed. The choice of the most appropriate means of transport for cargo transportation based on intermodality and multimodality, in particular rail, sea, and inland water transport, has been justified. Conclusions. The scholarly and applied approach has been proposed to identify the interdependence of manufacture, intermodal and multimodal cargo transportation of products. It can be used to increase the competitive advantages of Ukraine’s transit potential.